دراسة تجريبية لمدى تأثير درجة ميلان عمود تبادل الطاقة في نظام تحويل طاقة أمواج بحرية على مردوده وفقاً لظروف الساحل السوري. - كفا, سمير; عمران, عدنان; سليمان, منذر (Latakia University Journal -Engineering Sciences Series, 2016)
This research includes designing and executing of an applied model for converting the energy of the offshore sea waves into electrical power. The model runs according to oscillating water column system (OWC) using air turbine, which rotates by the air pressure generated by the sea waves within the energy chamber. The article studies the effect of technological changes on the efficiency of the model and subsequently the number of its turbine's rotation, within the wave parameters under the Syrian coast conditions. Results in form of clear curves and diagrams will be discussed. They will also be analyzed and considered to achieve a suitable suggestion that can improve the system in the futureيتضمن هذا البحث تصميم وتنفيذ نموذج تطبيقي يحَول طاقة الأمواج البحرية العرضية إلى طاقة كهربائية حيث يعمل النموذج تبعاً لنظام عمود الماء المتذبذب مستخدماً عنفة ويلز التيتستمد حركتها الدورانية من ضغط الهواء الذي تولده الأمواج البحرية في غرفة عمود تحويل الطاقة الخاص بالنظام المدروس.يشمل البحث,من خلال إجراء مجموعة تجارب على النموذج، دراسة تأثير بعض متغيرات النظام التكنولوجية على مردوده وبالتالي على عدد دورات العنفة العاملة فيه, وذلك ضمن بارامترات الموجة والشروط المناخية للساحل السوري, حيث تظهر النتائج على شكل منحنيات واضحة القيمة, ليتم التوصل من خلالها إلى توصيات ومقترحات مناسبة لتحسين النظام في المستقبل.